Systematics and floral micromorphology of core Aster and its related groups (Asteraceae, Astereae): Taxonomic significance and phylogenetic insights - Xinyu Chen; Tianmeng Qu; Xinyi Zheng; Yanru Zhang; Hui Chen; Bo Li; Liang Dou; Zhixi Fu (PhytoKeys)
Four floral microcharacters were examined within 40 species of core Aster and its related groups in the genus Aster L. (Asteraceae, Astereae). These microcharacters included corolla lobe, style base, endothecium cell wall thickening, and the relative length of the stigmatic line to sterile tip appendage of style branch. Phylogenetic analysis was performed using internal transcribed spacers (ITS), followed by ancestral traits reconstruction based on four microcharacters. The phylogenetic results supported the inclusion of Gymnaster, Heteropappus, Heteroplexis, Kalimeris, and Rhynchospermum within core Aster, as well as the possible segregation of groups B–D into multiple new genera within Astereae. Groups A (9 species) and C (4 species) displayed both equally and unequally lobed corollas. Group D (5 species) exclusively exhibited equally lobed corollas. Groups A (26 species), B (1 species), and D (5 species) included both types of swollen and unswollen style bases. Group C (3 species) displayed only unswollen style bases. Additionally, the endothecium cell wall thickenings and relative length of the stigmatic line to the sterile appendage were both highly variable among groups A–D. Given the complex variation of these floral microcharacters, the results of floral micromorphology and ancestral trait reconstruction indicated that the taxonomic significance of floral micromorphology within core Aster and its related groups is limited. However, specific micromorphological traits (e.g., unequally lobed corolla, radial thickening, and longer relative length) may be still useful for diagnosing particular species or groups. Therefore, floral micromorphology should be integrated with other types of evidence for more accurate infrageneric classification of Aster.